Using a hall accelerator to investigate d(d, n)3He and d(p, γ)3He reactions in the astrophysical energy region; Bulletin of the Russian Academy of Sciences: Physics; Vol. 74, iss. 4 - Bystritsky V. M.; Gerasimov V. V.; Krylov A. R.; Parzhitskii S. S.; Il’guzin D. A.; Anan’in P. S.; Dudkin G. N. Gennadiy Nikolaevich; Kaminsky V. L. Valery Ludvigovich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Petrov A. V.; Mesyats G. A. Gennady Andreyevich; et al. (2010, 2010)
Title screen